Laser heating of solid matter by light-pressure-driven shocks at ultrarelativistic intensities - Akli, K; Hansen, S; Kemp, A; Freeman, R; Beg, F; Clark, D; Chen, S; Hey, D; Hatchett, S; Highbarger, K; Giraldez, E; Green, J; et al. (2008)
The heating of solid targets irradiated by 5×1020Wcm-2, 0.8 ps, 1.05μm wavelength laser light is studied by x-ray spectroscopy of the K-shell emission from thin layers of Ni, Mo, and V. A surface layer is heated to ∼5keV with an axial temperature gradient of 0.6μm scale length. Images of Ni Lyα show the hot region has ≤25μm diameter. These data are consistent with collisional particle-in-cell simulations using preformed plasma density profiles from hydrodynamic modeling which show that the >100Gbar light pressure compresses the preformed plasma and drives a shock into the solid, heating a thin layer. © 2008 The American Physical Society.